ON THE ISSUE OF TRAINING FUTURE COMPUTER SCIENCE TEACHERS IN COMPUTER - Bidaybekov Е.Ы.; Khenner Е.К.; Shekerbekova Ш.Т.; Zhabayev Е. Х. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article discusses of training future computer science teachers in computer networks based on network simulation. Analysis of scientific and pedagogical and educational literature has shown that in the training of computer science teachers, computer networks are studied in the aspect of information simulation of their structures, while simulation the processes of their functioning is not given due attention, despite the possibility of its use in the organization of training. Most educational institutions face organizational, technical and material difficulties when organizing training in computer networks on real equipment. The above-mentioned difficulties in training future computer science teachers in computer networks can be avoided by using network simulation. By network simulation, we mean reproducing a dynamic image of the main network components (network cables, switches, hubs, routers, etc.) and visualization the processes of their configuration and operation on the computer screen.